Mengurai Permasalahan Pengelolaan Wakaf Uang pada Nazhir Perguruan Tinggi - Maesya Bani; Dede Abdul Fatah; Muhammad Hasbi Zaenal (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2024)
This research aims to look at the problems in the management of cash waqf managed by universities. As well as finding the best solutions and strategies that can be applied. Cash waqf which should be one of the Islamic social financial instruments that answers the problem of higher education costs, is currently not maximally managed. However, the practice of endowment funds has been applied by various universities abroad and in the country to support educational activities. This research uses the Analytical Network Process (ANP) method by taking data from expert respondents who are waqf experts. The total number of experts is 5 people who come from the background of regulators, academics and waqf practitioners. The results showed that the priority problem in the management of cash waqf managed by universities is the IT aspect. Starting from information technology, information systems and computerization of waqf databases. Followed by the issue of sharia, regulation, and then human resources. In terms of solutions, IT strengthening is a priority strategy for waqf management managed by universities. Then the strengthening of professional & certified Nazir human resources.